"The Fabric of our Lives": Catholic Church Perspectives on the Internet - McDonnell, Jim (Fieldwork in religion, 2009)
This paper is a first attempt to explore how a theology of communication might best integrate and develop reflection on the Internet and the problematic area of the so-called "information society." It examines the way in which official Church documents on communications have attempted to deal with these issues and proposes elements for a broader framework including "media ecology," information ethics and more active engagement with the broader social and policy debates.